Macroeconomic imbalances and exchange rate regime shifts - Erik Post (Uppsala University, Department of Economics, 2007)
This paper uses a dynamic stochastic rational expectations model of a small open economy to shed some light on factors determining exits from a fixed to a flexible exchange rate regime. Exits are in the model determined by a concern for macroeconomic stabilization. If cost-push shocks are important relative to demand shocks exits should occur more likely in times of low consumption and output, high interest rates, negative asset holdings, current account deficits, high inflation and high domestic prices. If the policy maker is more sensitive to negative rather than positive output deviations the probability of exits increases overall and is tilted toward exits with accompanying depreciation.
urn:nbn:se:uu:diva-25356
Keywords: E42; E44; E47; 330; exchange rates; exchange rate regimes; rational expectations model; Wirtschaftslage; Wechselkurspolitik; Rationale Erwartung; Dynamisches Modell